Microstructure and hardness properties of aluminum matrix composites reinforced with iron (iii) oxide nanoparticles and carbon nanotubes - Hanim, M.A. Azmah; S.N. Hadirah, Hadirah; Dele-Afolabi, T.T.; Jung, D.W.; Sapuan, S. M.; Jaafar, C.N. Aiza (Wiley, 2022)
This study focuses on the effects of iron (iii) oxide (Fe3O4) and multi-walled carbon nanotubes (MWCNTs) on the microstructure and hardness of aluminum matrix composites (AMCs). Aluminum matrix composites reinforced with iron (iii) oxide nanoparticles and multi-walled carbon nanotubes having sample formulation of aluminum-5iron (iii) oxide-xcarbon nanotubes (Al-5Fe3O4-xCNT; x = 0 wt.%, 0.01 wt.%, 0.05 wt.%, 0.1 wt.% and 0.5 wt.%) were prepared using the powder metallurgy technique. Microstructural characterization revealed that the aluminum-5iron (iii) oxide exhibited a better microstructure relative to the aluminum-5iron (iii) oxide-xcarbon nanotubes counterparts which exhibited a defective microstructure. More so, the hardness results showed that the aluminum-5iron (iii) oxide exhibited the highest hardness value of 48.32 HRH 60. However, the defective microstructure observed in the aluminum matrix composites reinforced with multi-walled carbon nanotubes can be attributed to the relatively lower hardness values of the aluminum-5Iron (iii) oxide-xcarbon nanotubes samples (22.87 HRH 60-40.24 HRH 60).